ASSESSMENT OF BACTERIAL PHOTODYNAMIC INACTIVATION MEDIATED BY METHYLENE BLUE IN THE PRESENCE OF POTASSIUM IODIDE - Dr. Alka Ekka; Dr. Vijaya Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: The increasing environmental problems associated with traditional methods of water disinfection, such as chlorination, have prompted the hunt for sustainable substitutes. Photodynamic treatment (PDT) with photosensitizers has emerged as a viable approach to water purification due to its advantages over conventional approaches. The objective of this research is to evaluate the effects of immobilized photosensitizers, specifically potassium iodide (KI) and methylene blue (MB), on improved long-term water disinfection and bacterial inactivation.Methods: When examining how photosensitizers affect bacterial inactivation, a methodical sequence of steps is utilized. Potassium iodide and methylene blue are co-extrusioned into a polymer matrix to create an efficient and safe immobilization procedure. The final beads undergo a thorough testing procedure that includes measurements of absorbance using UV-visible spectrophotometry, evaluation of photosensitizer leakage, and tests for antibacterial activity against both Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria.Findings: Examining photosensitizer in polymers reveals three different concentration gradients (C1, C2, and C3) with different amounts of methylene blue and potassium iodide. Following the deployment of the beads, data from the UV-visible spectrophotometer show an inverse relationship between absorbance and photosensitizer inclusion levels, with C1 showing the least inclusion and C3 the highest. Days 1 and 2 of the polymer matrix test show rapid leaking of photosensitizer, which is followed by a decrease in activity on the subsequent days. According to antibacterial activity tests, C1 is the concentration that works best for both types of bacteria, with C2 and C3 displaying different levels of potential for breakdown.Conclusion: The study comes to the conclusion that immobilised photosensitizers are very effective at disinfecting water and inactivating germs, especially when potassium iodide is present. For photosensitizer immobilisation, the suggested co-extrusion approach works well and is both economical and ecologically benign. Reactive iodine species are produced in conjunction with potassium iodide, which is thought to have a synergistic impact that improves bacterial death during methylene blue photodynamic therapy. This creative method, which highlights the use of potassium iodide and immobilised photosensitizers in environmental stewardship, has the potential to advance sustainable water disinfection techniques.